Comparative evaluation of open tray impression technique: investigating the precision of four splinting materials in multiple implants - Priyanka Patil; V. N.V Madhav; Abdulkhaliq Ali F. Alshadidi; Ravinder S. Saini; Lujain Ibrahim N. Aldosari; Artak Heboyan; Seyed Ali Mosaddad; Saeed Awod Bin Hassan; Saurabh Chaturvedi (BMC, 2023)
Abstract Background This study aimed to determine the relative positioning accuracy of multiple implants utilizing four distinct types of splinting materials. Methods The purpose of this in-vitro study was to compare the precision of four splinting materials in an open tray impression technique in multiple implant situations. Based on the material used for splinting, four groups were made (n = 40)- Group A: Conventional Method, Group B: Prefabricated Pattern Resin Framework, Group C: Prefabricated Metal Framework, Group D: Light Cured Pattern Resin, these groups were compared with the master model. A heat-cured clear acrylic resin and a master model were constructed. A pilot milling machine drill was used to drill four parallel holes in the anterior and premolar regions, which were later labeled as A, B, C, and D positions from right to left. Then, sequential drilling was carried out, and four 3.75‑mm diameter and 13-mm long ADIN implant analogs with internal hex were placed in the acrylic model using a surveyor for proper orientation. The impression posts were then manually screwed to the implant analogs using an open tray, and they were secured to the implants using 10 mm flat head guide pins with a 15 N.cm torque. 10 Open tray polyether impressions were made, and casts were poured. Each splinting method's distortion values were measured using a coordinate measuring machine capable of recordings in the X-, Y-, and Z-axes. Comparison of mean distances for X1, X2, and X3 was made using the Kruskal-Wallis test, and Pairwise comparison was done using Post Hoc Tukey's Test. Results The differences between the groups were significant when assessing the distances X1, X2, and X3 (p < 0.05). The comparison of deviations between the groups revealed a statistically significant difference (p < 0.05) for the deviation distance X3 but not for the deviation distances X1 and X2. For distance Y1, the difference between the groups was statistically significant (p0.05), but it was not significant for distances Y2 and Y3. A statistically significant difference was seen in the comparison between the groups (p < 0.05) for the deviation distances Y1, Y2, and Y3. The results were statistically significant for the distance Z1 comparisons, namely, control vs. Group A (p = 0.012), control vs. Group B (p = 0.049), control vs. Group C (p = 0.048), and control vs. Group D (p = 0.021), and for distance Z3 comparison for control vs. Group A (p = 0.033). The results were statistically insignificant for the distance Z2 comparisons (p > 0.05). Conclusions All splinting materials produced master casts with measurements in close proximity to the reference model. However, prefabricated pattern resin bars splinting showed the highest accuracy among the studied techniques. The most recent splinting techniques using prefabricated metal framework and light-cure pattern resin showed similar accuracy.